Integration of Islamic Educational Theology in Project Based Learning Strategies to Improve Student Spirituality - Nurhasan Nurhasan; Syukron Makmun; Ahmad Fauzi Zakaria; Adang Hambali; Andewi Suhartini (TA'DIB: Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the concept of integration of Islamic Education theology in the Project Based Learning (PjBL) strategy, its implementation in the learning process, as well as supporting and inhibiting factors in an effort to improve student spirituality. The research uses a qualitative approach with a descriptive type. Data was obtained through observations, in-depth interviews, and documentation of lecturers and students in the Bridge and Road Design Engineering Study Program, Department of Civil Engineering, Bandung State Polytechnic (Polban). Data analysis is carried out through data reduction, data presentation, and conclusion drawn. The results of the study show that the integration of Islamic Education theology in the PjBL strategy is realized through strengthening the values of monotheism, worship, and morals in each stage of project-based learning. Implementation is carried out systematically through the planning, implementation, monitoring, and evaluation stages by using the Qur'an and hadith as the normative basis of the project. This strategy is able to increase students' spiritual awareness, such as honesty, responsibility, social empathy, discipline, and awareness of worship. Supporting factors include lecturer competence, student motivation, characteristics of PjBL, and religious academic culture, while inhibiting factors include time constraints, formal academic orientation, and differences in students' religious backgrounds. This research confirms that the integration of Islamic Education theology in PjBL is effective in forming students who excel intellectually and spiritually.